2020
DOI: 10.1007/s15010-020-01448-x
|View full text |Cite
|
Sign up to set email alerts
|

Early experience with remdesivir in SARS-CoV-2 pneumonia

Abstract: At present, there is no definitive antiviral treatment for coronavirus disease 2019 . We describe our early experience with remdesivir in four critically ill COVID-19 patients. Patients received a 200 mg loading dose, followed by 100 mg daily intravenously for up to 10 days. All patients had been previously treated with other antivirals before remdesivir initiation. One patient experienced a torsade de pointes requiring cardiac resuscitation and one died due to multiple organ failure. Three patients showed bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 6 publications
1
31
0
3
Order By: Relevance
“…However, capability of remdesivir to make the SARS-CoV-2 undetectable in nasopharyngeal and nasal swab samplings was shown in two Italian studies, with a time to negativity of 12 and 3 days, respectively. 65,66 Of note, although the Wuhan RCT did not show any significant difference between the remdesivir and placebo group, some serious concerns regarding the methodology and study design had been suggested, such as an insufficient sample size and several baseline differences between the two groups, which may have affected the final results. 67 The first and most rigorous clinical trial in the United States remdesivir once, daily, on day1, followed by 100 mg/IV/daily on days 2 to 10.…”
Section: Other Possible Treatments For Covid-19mentioning
confidence: 99%
“…However, capability of remdesivir to make the SARS-CoV-2 undetectable in nasopharyngeal and nasal swab samplings was shown in two Italian studies, with a time to negativity of 12 and 3 days, respectively. 65,66 Of note, although the Wuhan RCT did not show any significant difference between the remdesivir and placebo group, some serious concerns regarding the methodology and study design had been suggested, such as an insufficient sample size and several baseline differences between the two groups, which may have affected the final results. 67 The first and most rigorous clinical trial in the United States remdesivir once, daily, on day1, followed by 100 mg/IV/daily on days 2 to 10.…”
Section: Other Possible Treatments For Covid-19mentioning
confidence: 99%
“…13 Clinically, multiple case reports and series from Canada, Europe, Japan, and the United States have provided early promising results of treatment with remdesivir, usually in combination with other agents. [14][15][16][17][18][19] In the first reported double-blind, RCT of remdesivir, the time to clinical improvement was similar to the control group (hazard ratio, 1.27, 95% confidence interval, 0.89 to 1.80) but numerically shorter for patients treated within 10 days of symptom onset (hazard ratio, 1.52, 95% confidence interval, 0.95 to 2.43). This trial unfortunately did not attain the predetermined sample size owing to containment of the outbreak in China.…”
Section: Remdesivirmentioning
confidence: 99%
“…Other drugs described as having the potential to cause hepatotoxicity in COVID-19 included hydroxychloroquine (n=1, 12.5%), tocilizumab (n=2, 25%), and remdesivir (n=1, 12.5%). 12,18,[54][55][56][57][58][59] The methodological characteristics of the finalised studies were also analysed. The largest number of the studies were retrospective observational studies (n=26, 41.9%), followed by meta-analyses (n=10, 16.1%), case reports (n=9, 14.5%), case series (n=7, 11.3%), prospective observational studies (n=3, 4.8%), and others Table 1).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…According to Cai et al, 12 the use of lopinavir/ritonavir increased the likelihood of liver injury 4-fold. Durante-Mangoni et al 54 reported that remdesivir caused elevation of liver enzymes in three out of four patients, and Weber et al 57 suggested that drugs may play a role in precipitating acute liver failure. Administration of lopinavir/ritonavir and interferon was followed by progressive worsening of LFTs.…”
Section: Drug-induced Hepatotoxicity In Covid-19mentioning
confidence: 99%